Association between Toll-like receptor 9 signaling defect and developing post-infectious irritable bowel syndrome - Kotani, Satoshi; Mishima, Yoshiyuki; Kishimoto, Kenichi; Oka, Akihiko; Oshima, Naoki; Kawashima, Kousaku; Matsumoto, Kenjiro; Usuda, Haruki; Wada, Koichiro; Ishihara, Shunji (Frontiers in Immunology, 2025)
IntroductionPost-infectious irritable bowel syndrome (PI-IBS) is a functional gastrointestinal disorder that develops after intestinal infection. A follow-up study after a waterborne outbreak of gastroenteritis indicated involvement of specific genetic variants including toll-like receptor (TLR)9, although its pathophysiological role remains unclear.MethodsTo investigate the role of TLR9 in PI-IBS, Citrobacter rodentium was administered to wild-type (WT), and TLR2, 4, and 9 knockout (KO) mice. Six weeks after infection, visceral sensitivity was evaluated using barostat-based colorectal distention. Additional assessments include histological inflammation, intestinal permeability, gut microbiota, and colonic gene expression.ResultsOnly TLR9 KO mice developed significant visceral hyperalgesia despite findings indicating mild mucosal inflammation in the acute colitis phase and lack of persistent low-grade inflammation with hyperpermeability in the recovered phase. Microbiota analysis and fecal microbiota transfer demonstrated partial involvement of gut dysbiosis in PI-IBS development. Additionally, microarray, PCR, and immunohistochemistry findings showed that the expression levels of the bradykinin B1 and B2 receptors (BDKRB1 and BDKRB2) in colonic epithelium were significantly higher in infected TLR9 KO mice as compared to WT mice. Furthermore, administration of BDKRB1 antagonist R715 and BDKRB2 antagonist HOE 140 significantly suppressed visceral hyperalgesia.ConclusionTLR9 deficiency leads to bradykinin receptor upregulation in the colonic epithelium following infectious colitis, contributing to the development of PI-IBS. Inhibition of these receptors alleviated visceral pain, indicating that bradykinin receptor antagonists may offer a novel therapeutic strategy for PI-IBS.